Meaning Shifts in Baghdadi Dialect: A Lexical Pragmatic Approach (Journal of the College of Basic Education, 2022)
The present study investigates the semantic shift or meaning change of Baghdadi dialect based on a lexical pragmatic approach. Lexical pragmatic approach tries to give a systematic and explanatory account of pragmatic phenomena that are connected with semantic under specification of lexical items. The conceptual core of lexical pragmatics demands a formulation of conversational implicatures paired with the idea of semantic under specification of the lexicon and appropriate representation of contextual an encyclopedic knowledge( Wilson D lectures, 2006-07:1). This approach posses two sub theories lexical semantics and conversational implicuture. It is intended to: (1) collecting Baghdadi dialect’s meaning shift from different informants of Baghdadi dialect, (2) examine these words or phrases by using lexical pragmatic approach. The result shows that some of the words of Baghdadi dialect prove that they have undergone the process of meaning shift, some of the utterances turned to have either negative or positive meaning. The study shows that psychological assumptions of the context are very important for the interpretation of the meaning of a word which has been affected by semantic shift. The contextual knowledge of the hearer enables him to differentiate the various meanings of a word and eventually settle on the speaker’s intended meaning. Therefore, socio-cultural forces also allow people to come in contact under different circumstances, contribute to the shift in meaning of words in a language. The types of semantic shift present in Baghdadi dialect are narrowing and broadening. On the basis of the results a number of effects that led to the semantic shift are presented